CRP deposition in human abdominal aortic aneurysm is associated with transcriptome alterations toward aneurysmal pathogenesis: insights from in situ spatial whole transcriptomic analysis - Kim, Eun Na; Seok, Hee Young; Lim, Joon Seo; Koh, Jiwon; Bae, Jeong Mo; Kim, Chong Jai; Ryu, Ga-Hyeon; Ok, You Jung; Choi, Jae-Sung; Cho, Chung-Hyun; Oh, Se Jin (Frontiers in Immunology, 2024)
BackgroundWe investigated the effects of C-reactive protein (CRP) deposition on the vessel walls in abdominal aortic aneurysm (AAA) by analyzing spatially resolved changes in gene expression. Our aim was to elucidate the pathways that contribute to disease progression.MethodsAAA specimens from surgically resected formalin-fixed paraffin-embedded tissues were categorized into the AAA–high CRP [serum CRP ≥ 0.1 mg/dL, diffuse and strong immunohistochemistry (IHC); n = 7 (12 cores)] and AAA–low-CRP [serum CRP < 0.1 mg/dL, weak IHC; n = 3 (5 cores)] groups. Normal aorta specimens obtained during heart transplantation were used as the control group [n = 3 (6 cores)]. Spatially resolved whole transcriptomic analysis was performed, focusing on CD68-positive macrophages, CD45-positive lymphocytes, and αSMA-positive vascular smooth muscle cells.ResultsSpatial whole transcriptomic analysis revealed significant differential expression of 1,086, 1,629, and 1,281 genes between high-CRP and low-CRP groups within CD68-, CD45-, and αSMA-positive cells, respectively. Gene ontology (GO) analysis of CD68-positive macrophages identified clusters related to inflammation, apoptosis, and immune response, with signal transducer and activator of transcription 3 implicated across three processes. Notably, genes involved in blood vessel diameter maintenance were significantly downregulated in the high-CRP group. GO analysis of lymphocytes showed upregulation of leukocyte rolling and the apoptosis pathway, whereas, in smooth muscle cells, genes associated with Nuclear factor kappa B (NF-κB) signaling and c-Jun N-terminal Kinase (JNK) pathway were upregulated, and those related to blood pressure regulation were downregulated in the high-CRP group.DiscussionCRP deposition was associated with significant transcriptomic changes in macrophages, lymphocytes, and vascular smooth muscle cells in AAA, suggesting its potential role in promoting pro-inflammatory and apoptotic processes, as well as contributing to the degradation of vascular structure and elasticity.